Victory from God and to God and His people (Assyrian Wars are modeled) - abbod sammar, saad; Jabbar Aziz Altaie, Ali (Journal of College of Education, 2019)
This study highlighted the employment of mythology in the Assyrian Wars. The Assyrian kings portrayed the ongoing wars they lead as divine wars, trying to hide their true motives, waged by the gods and for their blessing. We reviewed the most important gods employed by the Assyrian kings in their wars. He will also discuss the use of mythology in all military actions they have been undertaking.